Crédito de carbono: consequências socioambientais de sua comercialização no Brasil - LIMA, Fernanda Maria Amorim Carvalho de (2017)
The objective of this work is to analyze the carbon market in Brazil showing the socio-environmental consequences of its commercialization, through a historical and analytical perspective of the Kyoto Protocol and its mechanisms of flexibility. The methodology used will be the qualitative research. The greatest concern will be with regard to deepening and how it will be understood by people. It will be sought to explain why, exploring what needs to be done through a bibliographical survey in books, dissertations and theses already done on the subject in the library of the Federal University of Maranhão and in the sector, in the CAPES portal and in the internet , as well as books on the subject that contribute and enrich the construction of the dissertation. The paper also focuses on presenting a brief history of sustainability, from the 1972 World Convention on Environment to the concept of sustainability today. Second, the Protocol of Quito and the Flexibility Mechanisms, objectives and principles that guide it. Third, the socio-environmental consequences of carbon credits in Brazil. Addressing the concept of carbon credit and its commercialization. These topics are organized in such a way as to answer the central question of the study, which is: what are the consequences of the carbon trade for Brazil? The main conclusion is that there is a possibility of significant financial gains, combined with environmental conservation. The importance of public policies that stimulate the investment in CDM has been evident so that the Country can participate fully in the world market as a supplier of certificates of emission reductions and also implement a policy of climate change.